2016
DOI: 10.1038/srep26689
|View full text |Cite
|
Sign up to set email alerts
|

A genetic polymorphism affects the risk and prognosis of renal cell carcinoma: association with follistatin-like protein 1 expression

Abstract: Few single nucleotide polymorphisms (SNPs) associated with the risk of renal cell carcinoma (RCC) have been identified, yet genetic predisposition contributes significantly to this malignancy. We previously showed that follistatin-like 1 (FSTL1) was significantly down-regulated in clear cell RCC (ccRCC), in particular metastatic ccRCC. In the present study, we systemically investigated the associations of the 6 SNPs within FSTL1-coding genomic region with RCC risk and postoperative prognosis. Age- and gender-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Renal cell carcinoma (RCC), originates from cells in the renal cortex and is the most common type of kidney cancer in adults worldwide, with ~270,000 new cases and ~116,000 RCC-associated mortalities each year (1,2). RCC is divided into three major subtypes, including clear cell RCC (ccRCC), papillary RCC and chromophobe RCC (3).…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma (RCC), originates from cells in the renal cortex and is the most common type of kidney cancer in adults worldwide, with ~270,000 new cases and ~116,000 RCC-associated mortalities each year (1,2). RCC is divided into three major subtypes, including clear cell RCC (ccRCC), papillary RCC and chromophobe RCC (3).…”
Section: Introductionmentioning
confidence: 99%
“…The human RCC cell lines (786-O and ACHN) were originally obtained from the American Type Culture Collection (Manassas, VA, USA). The human embryo kidney cell line 293T (293T) was purchased from the Type Culture Collection of the Chinese Academy of Medical Sciences YULIN LAI 1,2,5* , JING QUAN 1,3,5* ,CANBIN LIN 1,4,5 , HANG LI 1,5 , JIA HU 1,2 , PEIJIE CHEN 1,4,5 , JINLING XU 1,5 , XIN GUAN 1,5 , WEIJIE XU 1,5 , YONGQING LAI 1,5 and LIANGCHAO NI 1,5 (Shanghai, China). All of them were cultured in Dulbecco's modified Eagle's medium (DMEM; Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA), with 10% fetal bovine serum (FBS; GE Healthcare, Little Chalfont, UK), 1% glutamine and 1% antibiotics (100 U/ml penicillin and 100 mg/ml streptomycin; Gibco; Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) accounts for 3% of all malignant tumors; ~270,000 new cases are diagnosed and ~116,000 RCC-associated mortalities occur worldwide per annum (1,2). Furthermore, 25-30% of patients have already developed metastatic disease at the time-point of diagnosis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, experimental studies have shown that FSTL1 inhibition promotes apoptotis of lung cancer cells [13]. In contrast, FSTL1 exerts tumor-suppressive actions in ovarian and endometrial carcinogenesis and its expression is down-regulated in metastatic clear-cell renal-cell carcinoma [14,15]. Recent studies have also documented altered expression of FSTL1 in human CRC, but divergent results have been provided regarding the cell sources of the cytokine and its role in the regulation of CRC cell behavior [16][17][18].…”
Section: Research Papermentioning
confidence: 99%